The role of government agencies in empowering women-owned SMME's in selected municipalities in the Capricorn District of Limpopo Province - Mpe, Ramatsobane Innocent (My University, 2018)
The high unemployment rate in South Africa encourages citizens to be job creators rather than job seekers. It is often said that small businesses hold the key to economic growth. The South African government endeavours to accelerate economic growth, job creation and to address inequalities, through enterprise development and support. It created and enacted laws that seek to create an enabling environment for the growth and support of predominantly black, women, youth and people with disabilities owning small, medium and micro enterprises (SMMEs) and cooperatives. In ensuring support for SMMEs, the government of the Republic of South Africa promulgated the National Small Business Act (NSBA), Act 102 of 1996, which clearly outlines the support that national, provincial, local governments and private sector entities are compelled to develop and implement - programmes geared towards the support and promotion of SMMEs. Since 1996, these entities have developed programmes and projects that aim to implement support of SMMEs. Similarly, the government agencies that operate in the Capricorn District Municipality (CDM) have developed programmes in support of SMMEs and cooperatives as per the abovementioned Act. Most business owners are constantly faced with challenges, especially women-owned SMMEs. The role of government agencies and the implementation of relevant programmes and strategies to empower women-owned SMMES are explored. Despite the above-mentioned government initiatives, women-owned SMMEs are still facing challenges such as lack of financial support, inadequate infrastructure, access to market and other related problems. These challenges hinder their business initiatives and economic growth in the CDM. This research contributes to the public discourse regarding empowerment of SMMEs, with particular reference to women-owned businesses, and also to contribute to policy development in the promotion and support of SMMEs. A conceptual framework is also reviewed in the study, regarding the importance of government agencies, SMMEs and women empowerment to the development of the South African economy.
Thesis (M.Dev.) -- University of Limpopo, 2018
Keywords: Government agencies; Women-owned businesses; Small Medium Micro Enterprises; Government aid to small business; Business women; Entrepreneurship